Unexpected diversity in eukaryotic transcription revealed by the retrotransposon hotspot family of Trypanosoma brucei. Issue 4 (14th December 2018) - Florini, Francesca; Naguleswaran, Arunasalam; Gharib, Walid H; Bringaud, Frédéric; Roditi, Isabel
Abstract: The path from DNA to RNA to protein in eukaryotes is guided by a series of factors linking transcription, mRNA export and translation. Many of these are conserved from yeast to humans. Trypanosomatids, which diverged early in the eukaryotic lineage, exhibit unusual features such as polycistronic transcription and trans-splicing of all messenger RNAs. They possess basal transcription factors, but lack recognisable orthologues of many factors required for transcription elongation and mRNA export. We show that retrotransposon hotspot (RHS) proteins fulfil some of these functions and that their depletion globally impairs nascent RNA synthesis by RNA polymerase II. Three sub-families are part of a coordinated process in which RHS6 is most closely associated with chromatin, RHS4 is part of the Pol II complex and RHS2 connects transcription with the translation machinery. In summary, our results show that the components of eukaryotic transcription are far from being universal, and reveal unsuspected plasticity in the course of evolution.